Factors Affecting the Purchase Intention of Virtual Goods in Mobile Game Clash Royale - Limanto, Jeremy; Semuel, Hatane; Adiwijaya, Michael (Master of Management Study Program, Faculty of Business and Economics - Petra Christian University, 2018)
Concerning Indonesia‘s rapid growth of mobile internet usage and also a growing mobile game market, this research aims to analyze the influence of Customer-to-Customer interaction (C2C) towards the purchase intention of virtual goods in a mobile game. It proposes a conceptual model integrating variables that have been studied in previous research on purchase intention, consumer engagement, brand image, and also C2C interaction, the latter of which plays a critical role, but has received less mobile game attention. The conceptual model has been tested using SmartPLS to a database of 200 players in Indonesia. The results show that consumer engagement, brand image is associated with C2C interaction and purchase intention in mobile game Clash Royale.